From recipient to contributor: The story of a social justice leader in a Hong Kong primary school. (July 2014) - Szeto, Elson
This article presents a principal's story of social justice practice in a Hong Kong primary school. The narration accounts for the notion of social justice through his practice in various ways. Studying in a 'rooftop' primary school located in a public housing area in Hong Kong was the principal's salient memory of his first year of schooling in times of limited resources. Perhaps because of a change in education policy, he was subsequently transferred to a better school sponsored by a charitable organization under the subsidy scheme of the then colonial government. As a recipient, he found a great contrast between the two schools in terms of teaching and learning resources and school environments. The principal's personal educational experiences and teachers' educational ideology sowed the seeds of social justice in his mind. Thirty-six years later, he returned to serve his old primary school as a contributor to social justice for the students and the community in which the school is located. The story suggests how the principal made sense of social justice through his practice. It reflects the values of social justice which benefit not only students and teachers but also the community with equity and equality in education.